PARTICIPATIVE LEADERSHIP AND ITS ROLE IN THE PERFORMANCE OF STUDENT ACTIVITY OFFICIALS IN SOME IRAQI UNIVERSITIES FROM THE PERSPECTIVE OF EMPLOYEES - Assist. Prof. Dr. Zeyad Hameed Abd; Assist. Prof. Dr. Zeyad Hameed Abd (Proximus Journal Publishing, 2024)
The study sought to determine the extent to which extracurricular activity authorities at certain Iraqi universities used participatory leadership, as well as to discover the variations in this degree of application. Given the nature of the study, the researcher used a descriptive method. The research community was made up of personnel from various Iraqi universities who worked in the sports industry. There were 110 people in the sample that were chosen at random. A scientifically constructed questionnaire with three dimensions and thirty statements was created. The questionnaire was prepared for use with the research sample after being validated using scientific processes. The results of the research indicated that the degree of use of participative leadership by student activity officials in some Iraqi universities was high. Furthermore, the degree of use of participative leadership by these officials increased with higher educational qualifications
Keywords: Participative Leadership; Extracurricular Activities; Student Activities; Sports Activities